Identificação arquivística: uma análise dos documentos produzidos pelo 10º Batalhão de polícia Militar do Estado do Pará - SANTOS, Nelson Júnior da Silva (2019)
This research aimed at observing the documents produced and processed in the archive of the 10th Battalion of the Military Police of the State of Pará in order to elaborate an archival policy within the scope of this institution. For the theoretical and practical subsidy, literature surveys were carried out in the area of archival identification. Exploratory and qualitative research, applying the methodology of case study, using technical procedures of documentary research and using data collection using questionnaire and observation. The research results point to the lack of archival criteria adopted in the four sectoral archives located in the 10th BPM/PA, which provides failures in documentary recovery, causing problems for the administration of the organ, the institution does not provide adequate space for the archiving of its documentary mass , nor of an archivist that guarantees the applicability of techniques that can directly aid in the treatment of the generated documents. We suggest that the institution create an archiving policy establishing the study of its documentary types, where it will be able to understand the configuration that the documentary species assumes according to the activity that generated it, the nature of the content, or the registration technique. From this practice of documentary identification instruments, such as a Classification Plan and the Temporality Table can be created aiming at the needs of the institution. The flowcharts produced from this analysis can serve as a guide for better organization and management of the documentary mass located in these sectors. Finally, the work emphasizes that, despite the limitations, from the above mentioned procedures, the analyzed files of the PMPA can obtain considerable improvement, expanding them to other collections of the institution.